1970
DOI: 10.3126/kuset.v3i2.2890
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Biochemical Changes in the Fresh Water Fish, <i>Catla catla</i> (Hamilton) Exposed to the Heavy Metal Toxicant Cadmium Chloride

Abstract: Cadmium (Cd), one of the twenty three heavy metal toxicants, is widely used in Ni-Cd batteries manufacture, metal and mining industry, dentistry etc. because of its non-corrosive nature. Cd is released in considerable amounts through industrial effluents into soil, surface and ground water systems. These excess amounts in addition to naturally occurring levels gradually build up to toxic levels causing damage to the biota of the aquatic ecosystem. It shows biomagnification and has greater half-life periods. Cd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
62
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(85 citation statements)
references
References 23 publications
12
62
2
1
Order By: Relevance
“…While, the decreasing in glycogen content in the muscles may be due to the inhibition of hormones which contribute to glycogen synthesis. These results are in agreement with Sobha et al (2007) and Maharajan et al (2012). While, different observations were recorded by Kavidha & Muthulingam (2014), who observed a remarkable decline in the carbohydrates content due to its rapid utilization to meet the reduced energetic efficiency at long exposure to heavy metals.…”
Section: Total Carbohydratessupporting
confidence: 81%
See 2 more Smart Citations
“…While, the decreasing in glycogen content in the muscles may be due to the inhibition of hormones which contribute to glycogen synthesis. These results are in agreement with Sobha et al (2007) and Maharajan et al (2012). While, different observations were recorded by Kavidha & Muthulingam (2014), who observed a remarkable decline in the carbohydrates content due to its rapid utilization to meet the reduced energetic efficiency at long exposure to heavy metals.…”
Section: Total Carbohydratessupporting
confidence: 81%
“…This depletion may be explained on the basis of energy production during the pollutant toxicity through metabolic utilization of the ketoacids to gluconeogenesis pathway for the synthesis of glucose. These observations are similar to those obtained by Sobha et al (2007) and El-Nabarawy (2014), who attributed low protein to other several pathological processes including impairment in protein synthesis machinery, renal damage and elimination in hepatic blood flow or plasma dissolution. Unsimilar findings were notably by Zaghloul (2000), who reported increasing in total proteins in soft tissues of the fishes exposed to heavy metals.…”
Section: Total Proteinssupporting
confidence: 79%
See 1 more Smart Citation
“…7 worked on biochemical composition of Atlantic bonito at different stages of maturity. 8 investigated the effect of toxicant stress on fish biochemical concentration in exposed fish. Douglas et al, (2008) 9 observed the role of phospholipids in nutrition and metabolism of teleost fish.…”
Section: Introductionmentioning
confidence: 99%
“…This trace metal affects the physiology of fish due to its chronic exposure to waterborne sub-lethal levels cadmium as suggested by Ricard et al [26] in the rainbow trout and by Abedi et al [27] in common carp. Acute toxicity studies of cadmium on the edible carp, Catla catla conducted by Sobha et al [28] revealed significant changes in the biochemical constituents of the fish like glucose, glycogen, total proteins, lipids and free amino acids. Reports by Abdel-Moneim et al [29] on gills and liver of Oreochromis niloticus from polluted wetland environments, Saudi Arabia showed that bioaccumulation of Cd were mostly above the WHO reference values.…”
Section: Discussionmentioning
confidence: 99%